Determination of Normal Indicators Based on Computed Tomography, Considering the Individual Structural Characteristics of the Temporomandibular Joint - Mirza, Р. О.; Pavlenko, Е. М. (Actual Dentistry, 2025)
Abstract. In cases of pain-dysfunction syndrome, computed tomography (CT) of the temporomandibular joint (TMJ) allows for the objective detection of changes characteristic of pathology by comparing joint space dimensions between the right and left sides, as well as by determining the anterior, superior, and posterior positions of the articular head within the joint cavity. Establishing a correlation between the type of TMJ structure—based on joint space dimensions and morphometric parameters characterizing the shape of the articular tubercle—is essential before prosthetic treatment and the development of an orthodontic treatment plan, after which verifying the position of the articular head within the joint socket is mandatory. Material and Methods. To determine the dimensions of the anterior, superior, and posterior joint spaces, CT of the temporomandibular joint was performed in 89 patients. CT images were obtained under normal occlusal conditions before deprogramming of the masticatory muscles and were repeated in the same patients before brace removal and prosthetic treatment. Based on the results obtained after deprogramming, the ratio between the articular head and the articular fossa was calculated, where values from –12% to +12% indicated a central position. Measurement of joint spaces in the sagittal projection was performed using two different methods of placing marker lines on CT images. Patients were grouped according to the height of the articular tubercle. To characterize the individual structural parameters of the articular tubercle in normal occlusion before deprogramming, the AEI-BFL and AEI-TRL angles were used, with the difference between these angles playing a key role. Results. The dimensions of the anterior, superior, and posterior joint spaces measured by two different methods completely coincided in patients with an articular tubercle height of up to 5.1 mm, and in 93.2% of cases with a tubercle height of 5.2–10 mm. Two variants of the central position of the articular head within the joint socket were identified after deprogramming the masticatory muscles and fixation with a bite block during CT examination. In the central position with reduced joint spaces, the anterior and posterior joint spaces measured 1.97 ± 0.22 mm (right side), 1.91 ± 0.21 mm (left side), 2.22 ± 0.21 mm (right side), and 2.29 ± 0.17 mm (left side). In the central position with enlarged joint spaces, the anterior and posterior joint spaces measured 2.7 ± 0.48 mm (right side) and 2.7 ± 0.46 mm (left side), and 2.9 ± 0.41 mm (right side) and 2.9 ± 0.45 mm (left side). Conclusions. The size of the anterior joint space, measured by two different methods, does not match when the articular tubercle height is 7.8 mm, provided that the width of the articular head is less than its height. The central position of the articular head within the fossa with reduced joint spaces is associated with a TMJ structural type determined by the difference between the AEI-BFL and AEI-TRL angles within 16 ± 7 degrees, provided that the width of the articular head is greater than or equal to its height. The central position with enlarged joint spaces corresponds to a TMJ structural type determined by the difference between the AEI-BFL and AEI-TRL angles within 29 ± 6 degrees, provided that the width of the articular head is greater than or equal to its height.